MEMBANGUN KARAKTER KREATIF PADA SISWA SEKOLAH DASAR MELALUI PEMBUATAN KIPAS DENGAN MOTIF BATIK KALIMANTAN TENGAH - Lutfia Maulida; Setria Utama Rizal (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
Of the 18 existing character values, one of them is the creative character value. Creative character has an important role in shaping student character and creativity. The aim of this service is expected to be to build students’ creativity to be creative and express themselves through art, and to introduce students to Central Kalimantan batik motifs as part of their cultural identity. The method used is presentation of the material, then continued with practice. This service activity was carried out for one day, namely on Friday 18 October 2024 at SD IT Al-Furqan Palangka Raya, involving grade 5 students of Ibnu Qoyyim SD IT Al-Furqan Palangka Raya. The result of this activity is that students are creative and express themselves through art, and can provide direct experience in making handicrafts. Through this activity, students did it enthusiastically and enthusiastically.